Push-out bond strength of a fiber post system with two resin cements - Ramin Mosharraf; Alireza Haerian (Wolters Kluwer Medknow Publications, 2011)
Introduction: Debonding is a common cause of failure encountered with fiber-reinforced composite (FRC) posts, and usually occurs along the post space-dentin adhesive interface. The aim of this in vitro study is to evaluate the regional push-out bond strength of a fiber-reinforced post system, using two resin cements. Materials and Methods: In this in vitro study 20 maxillary central incisors were decoronated and the roots were endodontically treated. Following post space preparation, the roots were divided into two groups of 10 specimens each. Fiber-reinforced composite posts were cemented with two resin cement systems: (a) Self-etch system (Panavia F2.0/ED-primer II) and (b) conventional system (Variolink II/Excite DSC). Three slices of each root, with a thickness of 3 mm, were prepared. The push-out test was performed with a universal testing machine at a crosshead speed of 1 mm/ minute, and bond strength values were calculated. The data were analyzed with a two-way Analysis of variance (ANOVA) and Scheffe tests (α=.05). Results: There were no significant differences between the mean push-out bond strengths of two experimental groups (Panavia F: 12.59±5.44, Variolink II: 12.49±4.52 MPa) (P=0.920), but there were significant differences between the mean push out bond strengths of the root dentin regions (P<0.001). Conclusion: Under the conditions of this study, there was no significant difference between the mean push out bond strength of self-etching and the conventional resin cement systems. The coronal region of the root dentin showed a significantly higher bond strength than the apical region.